Implementasi Program Cek Kesehatan Gratis Di Pelayanan Kesehatan Primer: Studi Literatur - Syafrina Ulfah; Nurcholisah Fitra (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2026)
The Free Health Check-up (CKG) is a government program designed to strengthen promotive and preventive health efforts through the early detection of risk factors, pre-disease conditions, and diseases across the community according to the life-cycle approach. As a relatively new initiative, the implementation of the CKG program in primary healthcare settings still requires further evaluation to assess implementation readiness, digital support systems, and community participation. This literature review aimed to examine the implementation of the Free Health Check-up Program in primary healthcare services. Relevant literature was retrieved from the Google Scholar database using the keyword "implementation of the free health check-up program" and was limited to open-access, full-text articles published between 2025 and 2026. The search identified eight eligible articles, which were extracted and analyzed in this review. The synthesis revealed three major themes in the implementation of the CKG program: (1) primary healthcare service readiness, (2) digitalization and reporting systems, and (3) community participation and communication strategies. Primary healthcare readiness includes the availability of human resources, infrastructure, medical equipment, consumable medical supplies, funding, service workflows, and cross-sectoral coordination. Digitalization through the SATUSEHATplatform and integrated reporting systems has the potential to improve service efficiency; however, challenges remain regarding digital literacy, internet connectivity, and the technical capacity of healthcare personnel. Community participation is influenced by knowledge, attitudes, the roles of community health volunteers, teachers, healthcare workers, and communication strategies tailored to the characteristics of the target population. The successful implementation of the CKG program requires strengthening primary healthcare systems, optimizing digital health platforms, and adopting community-based communication strategies to ensure the program is more effective, inclusive, and sustainable.